TECKNOLOGI PEDAGIGICAL AND CONTENT KNOWLEDGE (TPACK) DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Riswan; Mardia Hayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
echnological advancements in the era of the Industrial Revolution 4.0 require teachers, including Islamic Religious Education (IRE) teachers, to possess pedagogical competencies integrated with technological mastery and subject matter knowledge. One relevant conceptual framework to address these demands is Technological Pedagogical Content Knowledge (TPACK). This study aims to examine the concept, components, learning models, types of technology, and the integration of TPACK in Islamic Religious Education learning, as well as to identify factors that hinder its implementation. The method employed in this study is a literature review by analyzing various relevant sources, including books and scholarly articles. The findings indicate that TPACK represents a synthesis of technological knowledge, pedagogical knowledge, and content knowledge that interact with one another to create effective, innovative, and contextual Islamic Religious Education learning. The implementation of TPACK in Islamic Religious Education can be carried out through various learning models, such as blended literacy, discovery learning, inquiry learning, problem-based learning, digital game-based learning, and video-based learning. The integration of TPACK has been shown to enhance students’ learning motivation and support the achievement of cognitive, affective, and psychomotor competencies. However, the implementation of TPACK still faces several challenges, including teachers’ limited pedagogical and technological competencies, as well as insufficient supporting facilities and infrastructure. Therefore, strengthening TPACK competencies among Islamic Religious Education teachers is a strategic necessity to improve the quality of learning in the twenty-first century.